Формування стратегії управління підприємством з виробництва твердого біопалива - Галиш, Наталія Андріївна; Galish, N. A. (Тернопіль : ТНЕУ, 2019)
Узагальнено наукові підходи до формування стратегічного управління підприємством з виробництва твердого біопалива, що функціонує в умовах сталого розвитку. Здійснено оцінку та аналіз процесів стратегічного управління на підприємстві з виробництва деревних пелет і розкрито методи вдосконалення процесу формування стратегії розвитку підприємства. Визначено сутність стратегічного управління виробничим підприємством, зокрема узагальнено сучасні підходи до формування стратегії управління підприємством та його трансформації в контексті сталого розвитку економіки, а також встановлено основні фактори впливу на формування цієї стратегії. Проаналізовано тенденції розвитку біоенергетичної галузі, систематизовано організаційно-технологічні особливості виробництва деревних пелет, побудовано ланцюг створення вартості біопалива. Проведено діагностику виробничої діяльності підприємств з виробництва твердого біопалива в Україні. Здійснено оцінювання внутрішнього й зовнішнього середовищ діяльності підприємств. Сформовано та обґрунтовано алгоритм побудови стратегії управління підприємством з виробництва твердого біопалива. Побудовано інтервальну дискретну модель динаміки частки підприємства на ринку твердого біопалива. The thesis describes the author's approach to the formation of a strategy for the management of solid biofuel production that operates under conditions of sustainable development and produces one of the end-energy source which is renewable. At the same time, the implementation of evaluation and analysis of the processes of strategic management at the enterprise and methods of improving corporate management systems should be considered as a substantially significant contribution of the thesis. In the optimal management model for a biofuel production company, it is proposed to carry out a comprehensive strategic analysis of the three areas of the external environment – the external macro environment of the firm (legal framework, state regulation, including tax, investment climate), branches of traditional and alternative fuels (availability of specific regulation features, availability of standards and technical regulations) and market conditions (analysis of demand and supply of products, consumer properties of the product). This allows obtaining the necessary statistical data, to identify the impact of external and internal factors on the company's activities, to identify the main trends in the industry, and thereby improve the quality of the information received. It is suggested that the choice matrix of the enterprise’s strategic development is based on the assessment of its strategic potential and the impact on it of external unpredictable factors. The author determines that the management strategy of enterprises is engaged in the production of solid biofuels, conceptually affects some specific features and determines its transformation. Taking into account the wide scope of enterprise’s objectives and formulating proposals for the development of a development strategy, it is suggested that the quality of the transformation of an existing management scenario should depend on ranking priorities of the enterprise. It is important to determine the level of their coherence with the corporate general strategy. For a solid biofuel company, the basis for selecting such criteria is to put the business processes of the raw materials supply (biomass delivery), production, storage and distribution of end-products (solid biofuels). Furthermore, the trends in the development of the biofuels market (the ratio of demand and supply to biofuels) at the regional, national and international levels should be taken into account. The main purpose for an enterprise producing wood pellets is to generate profits and increase the share of presence at the biofuel market. Objectively, for the enterprises producing wood pellets, which work both on the domestic and on the external market, the main objective of activity corresponds to the basis of value creation of the product, which may include not only the main stages (production, sales), but also additional stages (sale of equipment running on pellets, after-sales-service, etc.), which greatly scales this market branch. The paper proposes to use the principles of interval arithmetic and methods of analysis of interval data. It is argued that since data on the dynamics of the market share of commodity products , as well as the share of the market for consumable raw materials, cannot be considered as clearly defined from the statistical point of view, it is expedient to represent these factors within a certain range of meanings, bearing in mind that their true unknown value is within a specified interval. It is revealed that the key role by the process of making strategic decisions due to the key goals of the enterprise is played by such aspects as: the level of supply and demand, the provision of raw material by the enterprise, production and inflation expectations, the seasonal demand and supply, the buyers' preferences, investment intentions, buying stereotypes about the origin of products. It is also proved that the use of the fuzzy set theory to determine the optimal assortment of products for a wood pellet production company in the context of implementing its general strategy will allow us to clearly adhere to the key strategic goals for the production of pellets by giving up non-promising types of products and will change the structure of the assortment towards the most demanded products.
Formation of a management strategy for the production of solid biofuels
Keywords: стратегія управління підприємством; стратегічне управління; стратегічний менеджмент; стратегічне планування; тверде біопаливо; біоенергетична галузь; біоенергетичний ринок; пелети; сталий розвиток; альтернативні види палива; enterprise’s management strategy; strategic management; strategic planning; solid biofuel; bioenergy branch; bioenergy market; pellets; sustainable development; alternative fuels